Analisis Kesulitan Belajar Siswa Pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas IV Sekolah Dasar - Lusi Adi Wahyuni; Ika Candra Sayekti (Universitas Negeri Padang, 2023)
The researcher's aim is to analyze students' learning difficulties regarding plant reproduction in science subjects in class IV elementary school. The method used is qualitative with a phenomenological research design. Data collection techniques were carried out through observation, interviews & documentation. Data analysis techniques through data collection, data reduction, data presentation & drawing conclusions. Validity of data using source & technique triangulation methods. The research instrument was carried out using observation, interviews & documentation. The results of the research show that students have difficulty learning plant breeding material in science subjects in grade IV elementary school, namely: 1) there are difficulties in plant breeding material, sub-topics of plant reproduction; 2) difficulty factors that influence difficulty learning plant breeding material are: a) internal factors : students' motivation to learn in class is still lacking so students ignore the teacher's explanations in class, students' intelligence is quite low in absorbing the material explained by the teacher, students' lack of interest in learning because students are bored; b) external factors: lack of school facilities & infrastructure, teachers' learning methods are less attractive, environmental factors students prefer to play games, family factors lack of attention from parents who are busy working; c) psychological factors include students who are less interested in learning because students are less able to read; d) physiological factors: students do not focus on learning because students have nearsightedness and students are slow in absorbing the material.